Inflation dynamics with labour market matching: assessing alternative specifications - Kai Christoffel; James Costain; Gregory de Walque; Keith Kuester; Tobias Linzert; Stephen Millard; Olivier Pierrard (National Bank of Belgium, 2009)
This paper reviews recent approaches to modeling the labour market, and assesses their implications for inflation dynamics through both their effect on marginal cost and on price-setting behavior. In a search and matching environment, we consider the following modeling setups: right-to-manage bargaining vs. efficient bargaining, wage stickiness in new and existing matches, interactions at the firm level between price and wage-setting, alternative forms of hiring frictions, search on-the-job and endogenous job separation. We find that most specifications imply too little real rigidity and, so, too volatile inflation. Models with wage stickiness and right-to-manage bargaining or with firm-specific labour emerge as the most promising candidates
Keywords: E31; E32; E24; J64; 330; Inflation Dynamics; Labour Market; Business Cycle; Real Rigidities; Inflation; Lohnrigidität; Arbeitsmarkt; Arbeitsuche; Unvollkommener Markt; Neoklassische Synthese; Theorie; Eurozone; EU-Staaten